Implementation of ODF (Open Defecation Free) Program in Warudoyong Sub-district, Sukabumi City - Zaimatuz Zulfa; Tuah Nur; Dine Meigawati (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study aims to examine how the implementation of the open defecation free (ODF) program in Warudoyong Sub-district, Sukabumi City. The Open Defection Free (ODF) program is a government program that aims to change hygienic and sanitary behavior through community empowerment so that the community independently improves good health status. The urgency of this research is due to the lack of public awareness of the importance of hygiene and health. In Warudoyong Sub-district, Sukabumi City, there are still people in two villages who practice open defecation. Based on data from the Sukabumi City Health Office, from 2019 to 2022 there was no decrease in open defecation rates in Nyomplong Village and Warudoyong Village. The research method used a descriptive qualitative method with a snowball sampling technique and the number of respondents was six informants. The result of this research is that the ODF program in Warudoyong Sub-district, Sukabumi City has not been running optimally, due to the lack of public awareness about the importance of the ODF program and limited land for the construction of communal septic tanks. Therefore, the recommendation for this research is the need for community roles and cooperation to improve facilities for the construction of communal septic tanks so that people can improve the quality of clean and healthy living, and increase socialization media by utilizing social media to provide information about the benefits of the ODF program to increase knowledge for the community.